Fostering Emotional Availability in Mother-Child-Dyads With an Immigrant Background: A Randomized-Controlled-Trial on the Effects of the Early Prevention Program First Steps - Lebiger-Vogel, Judith; Rickmeyer, Constanze; Leuzinger-Bohleber, Marianne; Meurs, Patrick (Frontiers in Psychology, 2022)
Background In many Western countries like Germany, the social integration of children with an immigrant background has become an urgent social tasks. The probability of them living in high-risk environments and being disadvantaged regarding health and education-related variables is still relatively higher. Yet, promoting language acquisition is not the only relevant factor for their social integration, but also the support of earlier developmental processes associated with adequate early parenting in their first months of life. The Emotional Availability Scales (EAS) measure the quality of caregiver-child-interactions as an indicator of the quality of their relationship and thus of such early parenting, focusing on mutual and emotional aspects of their interaction. Method This pilot study examined in a randomized controlled trial the effects of the prevention project First Steps regarding the hypothesis that the Emotional Availability (EA) improved to a greater extent in “difficult-to-reach” immigrant mother-child dyads in a psychoanalytically oriented early intervention (A, FIRST STEPS) compared to a usual care intervention (B) offered by paraprofessionals with an immigrant background. A sample of N = 118 immigrant women in Germany from 37 different countries and their children was compared with regard to the parental EA-dimensions sensitivity, structuring, non-intrusiveness and non-hostility and the child dimensions responsiveness to and involvement of the caregiver in the pre-post RCT design. Results and Conclusion Different from what was expected, repeated ANOVAs revealed no significant pre-post group differences for the parental dimensions. For the child dimensions the effect of time of measurement was highly significant, which can be interpreted as mostly natural developmental effects. Still, on the level of simple main effects for each intervention, only in the FIRST STEPS groups child responsiveness significantly improved. When controlled for confounding variables, a significant interaction effect for maternal sensitivity in favor of the FIRST STEPS intervention was found. The systematic group differences indicate that the more extensive and professional intervention, focusing on the individual needs of the participants, is more suitable to support the quality of the mother-child-relationship amongst immigrant mother-child dyads than usual care. The results are discussed taking into account the context of the maternal migration process and potential maternal traumatization. Clinical Trial Registration [https://clinicaltrials.gov], identifier [DRKS00004632].